Factors affecting time performance of refurbishment projects in Singapore / Chew Lee Fuan - Chew, Lee Fuan (2012)
Refurbishment is becoming an important economic driver in Singapore’s construction industry due to existence of high number of ageing buildings, limited vacant land for new development and the rapid changes of technology used. There are limitations and even drawbacks to these efforts as the time required to complete the refurbishment projects is frequently greater than the time originally specified in the contract. The main purpose of the study is to identify factors affecting the time performance for refurbishment projects in Singapore. This study used mixed method approach with quantitative as the main data. Semistructured interviews that involved twenty projects were carried out to verify the project characteristics of refurbishment in Singapore. The result of the interviews was used to identify the project characteristics variables for the next stage of data collection. Onehundred (100) questionnaires were distributed to main contractors who have experience in refurbishment and a contract value of minimum two-hundred-and-fifty thousand dollars. Of those, 33 replied and were found to be useful for data analysis. Statistical Package for the Social Sciences (SPSS) was used to analyse the data. From the data analysis, three variables were found to be significantly correlated with time performance variable. They are non-payment of salary to workers causing slow down; conflict and disputes between contractor and superintending officer; and uncertainty and complexity of the project. From the correlation analysis result, a prediction model was developed using multiple regression analysis. The result indicated that to control the time performance of refurbishment projects in Singapore, three variables need to be given more attention through the equation of Time Performance= 0.945+ 0.076Finance-NP + 0.035Contractual-CD + 0.076Site-UC. From the findings, it could be concluded that the time performance of refurbishment projects is affected by the project characteristics. Thus, more focus probably needs to be given to those factors in order to improve the time performance of refurbishment projects in Singapore.